2013
DOI: 10.5943/mycosphere/4/2/12
|View full text |Cite
|
Sign up to set email alerts
|

Fungi on decaying leaves of Magnolia liliifera and Cinnamomum iners show litter fungi to be hyperdiverse

Abstract: Diversity of fungi on decaying leaves of Magnolia liliifera and Cinnamomum iners collected during the dry season at Doi Suthep-Pui forest, Chiang Mai, Thailand were studied and compared. Thirtyfive taxa were identified from Magnolia liliifera comprising 8 sexual (ascomycetes) and 27 asexual taxa. The most abundant species found were Sporidesmium sp., Colletotrichum fructicola and Stachybotrys parvispora. Seventeen taxa were identified from Cinnamomum iners comprising 2 ascomycetes and 15 asexual taxa. Anamorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…(2005) found distinct communities among five plant species, with a complementary level of 68% for the 10 most frequently isolated fungi. Monkai et al (2013) reported very low levels of similarity between the communities of Magnolia liliifera and Cinnamomum iners , reaching values of 1.92% to 8.51%, considering species and genus, respectively. Pasqualetti et al (2014)investigated the fungi of 17 species of trees in Mediterranean areas and observed communities with variable percentages of overlapping species (6-47%).…”
Section: Discussionmentioning
confidence: 94%
“…(2005) found distinct communities among five plant species, with a complementary level of 68% for the 10 most frequently isolated fungi. Monkai et al (2013) reported very low levels of similarity between the communities of Magnolia liliifera and Cinnamomum iners , reaching values of 1.92% to 8.51%, considering species and genus, respectively. Pasqualetti et al (2014)investigated the fungi of 17 species of trees in Mediterranean areas and observed communities with variable percentages of overlapping species (6-47%).…”
Section: Discussionmentioning
confidence: 94%
“…The study of saprobic fungi on dead leaves of M. liliifera found that Ophioceras cf. leptosporum MFLU 10-0281 and Fusicoccum aesculi MFLU10-0260, MFLU10-0266 were observed on young and mostly decaying leaves (Monkai et al 2013). The results showed that these fungal isolates are strong decomposers because they grow on the leaves over the decay process.…”
Section: Resultsmentioning
confidence: 87%
“…Six saprobic fungal strains were isolated from dead leaves of Magnolia liliifera collected from Doi Suthep-Pui forest, Chiang Mai, Thailand (Monkai et al 2013…”
Section: Fungal Strains and Test Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several novel fungi have been reported from the tropics suggesting that there are still fungi in tropical forests awaiting discovery and analysis (Hawksworth 2002). In Thailand, there have been several studies of microfungi on plants that have discovered many new fungi (Doilom et al 2017;Kodsueb et al 2007aKodsueb et al , 2007bKodsueb et al , 2006Monkai et al 2013;Pinnoi et al 2007Pinnoi et al , 2006Seephueak et al 2011Seephueak et al , 2010Tibpromma et al 2016).…”
Section: Introductionmentioning
confidence: 99%